Localizadores apicales y su impacto en la disminución de fracasos endodónticos. - Garces Gualaquiza, Ana Yajaira (2023)
Apical locators are essential tools in endodontic dentistry, used to accurately determine the working length of root canals. These devices enable endodontists to accurately identify the position of the apex, that is the tip of the tooth root. Their use offers a number of significant advantages in the field of endodontics, contributing to the reduction of procedural failures. The fundamental purpose of this research is to comprehensively evaluate how the use of apical locators can influence the reduction of endodontic failures. This review aims to provide an updated view based on the available scientific literature. To address this topic, a comprehensive literature review was conducted using a qualitative methodology that included the collection of information from 62 articles from various sources such as PubMed, Scielo, Elsevier and Google Scholar. The findings revealed that apical locators prove to be highly effective in accurately determining working length compared to conventional methods such as radiographs. These devices contribute significantly to reducing root canal under-instrumentation, and crucial factors related to endodontic failures. Although a minimum failure rate of 10% to 14% has been observed in recent years, this figure can be influenced by multiple variables, such as the skill of the endodontist, the anatomical characteristics of the tooth, the use of materials and adequate disinfection, among others. However, thanks to current technological advances and techniques, a high degree of success has been achieved in endodontic treatments.